2020
DOI: 10.3390/nano10101908
|View full text |Cite
|
Sign up to set email alerts
|

Your Spreadsheets Can Be FAIR: A Tool and FAIRification Workflow for the eNanoMapper Database

Abstract: The field of nanoinformatics is rapidly developing and provides data driven solutions in the area of nanomaterials (NM) safety. Safe by Design approaches are encouraged and promoted through regulatory initiatives and multiple scientific projects. Experimental data is at the core of nanoinformatics processing workflows for risk assessment. The nanosafety data is predominantly recorded in Excel spreadsheet files. Although the spreadsheets are quite convenient for the experimentalists, they also pose great challe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 16 publications
0
24
0
Order By: Relevance
“…By offering a consistent terminology throughout a subject, ontologies are used to facilitate communication between people and organizations [ 39 ]. The most used nano-specific ontologies are the NanoParticle Ontology (NPO) and the eNanoMapper (eNM) ontology [ 26 , 40 ]. All descriptors in the measurement and instrument tabs are semantically annotated (see Supplementary Materials, tab Dictionary ), to supplement the metadata.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By offering a consistent terminology throughout a subject, ontologies are used to facilitate communication between people and organizations [ 39 ]. The most used nano-specific ontologies are the NanoParticle Ontology (NPO) and the eNanoMapper (eNM) ontology [ 26 , 40 ]. All descriptors in the measurement and instrument tabs are semantically annotated (see Supplementary Materials, tab Dictionary ), to supplement the metadata.…”
Section: Resultsmentioning
confidence: 99%
“…All descriptors in the measurement and instrument tabs are semantically annotated (see Supplementary Materials, tab Dictionary ), to supplement the metadata. The descriptors can be annotated with several ontological terms, allowing the usage of numerous dictionaries to improve interoperability [ 40 ]. We combined and integrated different ontological IDs from diverse libraries when a single annotation from a source was missing.…”
Section: Resultsmentioning
confidence: 99%
“…Since available Comet in vitro data have been generated in the last decade by different laboratories within different research initiatives, and reported in diverse formats and without the use of controlled vocabularies, many inconsistencies in the terminology exist ( e.g. , naming of materials, endpoint, methods, cell types, concentrations, time points, etc…) [65] . Examples of lack of controlled vocabularies and standardization in the reported data are displayed in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The definition of the methods, protocols and parameters that guide data generation is in fact evolving together with knowledge on the determining factors of the physico-chemical and toxic effects. The eNanoMapper database and related tools are ongoing efforts to improve the FAIRness of data infrastructures (Kochev et al, 2020). One of the strengths of this FAIR-compliant data repository is the creation of a communication channel between laboratory experts and data modelling experts to maximize the understanding, exchange, availability and, ultimately, the reuse of data.…”
Section: Meeting Reportmentioning
confidence: 99%